(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Blockchain technology is increasingly recognized as a transformative tool for ensuring transparency and traceability in the food supply chain. This abstract provides a concise overview of the theoretical foundations, practical applications, challenges, and future directions of blockchain technology in the context of the food industry. Blockchain technology offers a decentralized and immutable ledger system, providing a novel solution to challenges related to transparency and traceability in supply chain management. Theoretical perspectives from various disciplines, including information systems, economics, and operations management, underscore the potential of blockchain to enhance trust and accountability in the food supply chain. Blockchain technology finds diverse applications in the food supply chain, including tracking and tracing the origin of food products, ensuring food safety and quality control, facilitating fair trade and ethical sourcing practices, reducing food waste, and enhancing consumer trust and engagement. These applications demonstrate the transformative potential of blockchain to revolutionize supply chain management in the food industry, improving efficiency, transparency, and sustainability. While blockchain technology offers significant benefits for the food supply chain, its implementation faces challenges such as technical barriers, scalability issues, regulatory considerations, privacy concerns, and interoperability challenges. Addressing these challenges presents opportunities for innovation, collaboration, and regulatory reform, leading to substantial improvements in food safety, sustainability, and consumer welfare. Emerging trends such as the integration of blockchain with other technologies like Internet of Things (IoT), artificial intelligence (AI), and big data analytics offer promising avenues for future research and innovation in the food industry. However, there are still gaps in our understanding of how blockchain technology can be applied effectively in different contexts, the impact of regulatory frameworks on blockchain adoption, and the scalability and interoperability of blockchain solutions. Continued research, collaboration, and innovation are essential to unlocking the full potential of blockchain technology for ensuring transparency and traceability in the food supply chain.